Effects of Nifedipine Tablets Combined With Magnesium Sulfate on Blood Coagulation Index, Oxidative Stress, NO and ET-1 Levels in Patients With Pregnancy Hypertension - Yu, Xiaomei; Zhou, Qiang (Frontiers in Surgery, 2022)
Pregnancy-induced hypertension syndrome (PIH) is also known as pregnancy-induced hypertension. It usually occurs at 20 weeks of gestation or 2 weeks after delivery. In addition to high blood pressure, it can also be accompanied by edema, proteinuria, thrombocytopenia, and liver Clinical manifestations such as functional impairment. To explore the effects of nifedipine tablets combined with magnesium sulfate on blood coagulation indexes, oxidative stress and levels of NO and ET-1 in patients with pregnancy-induced hypertension. A total of 110 patients with hypertension during pregnancy were admitted to our hospital from January 2020 to January 2021. According to the random number table method, 110 patients were divided into control group and treatment group, with 55 cases in each group. The blood pressure levels (systolic and diastolic blood pressure), coagulation indexes (TT, PT, APTT, Fib), oxidative stress indexes (LPO, MDA, SOD), vascular endothelial function (ET-1, NO) and clinical efficacy. The results showed that nifedipine tablets combined with magnesium sulfate in the treatment of pregnancy-induced hypertension can improve the blood coagulation function of patients, reduce oxidative stress damage, adjust the serum levels of ET-1 and NO, and improve the clinical efficacy.